Desynchronization in a cardiac resynchronization device induced by a pacemaker-mediated tachycardia algorithm - S. Serge Barold; Nigel Lever; Fiona Riddell; Andreas Kucher (Indian Pacing and Electrophysiology Journal, 2018)
This report describes the occurrence of desynchronization in a patient with a cardiac resynchronization device programmed with an active pacemaker-mediated tachycardia algorithm based on AV delay modification. Desynchronization was precipitated by sinus tachycardia and the abrupt return of the prevailing AV delay that followed the periodic prolongation of the AV delay mandated by activity of the algorithm. Prevention of desynchronization in this setting requires programming a right ventricular upper rate interval longer than the sum of the programmed ventriculoatrial interval and the AV delay.